(untitled) (Research, Society and Development, 2022)
We intend to analyze the prediction of Recycling Habits (HR) from the Attitudes and Beliefs in Recycling (ACR), and the Awareness of Individual Consequences (ICC). A total of 352 people participated in the study, who responded on a five-point Likert-type scale, the Self-Reported Habit Index (HAI), CCI and ACR scales. In SPPS 25.0 software, descriptive statistics, factor analysis were performed and in AMOS 24.0, the calculation of Structural Equations. The results showed that the ACR has an influence on the ICC, which in turn influences the HR. These results aim to contribute in the theoretical scope to a better understanding of recycling habits in families living far from their country of origin; in the field of practice, it suggests both for the formulation of public policies and for the development of campaigns of social engagement.